STUDY OF USING CANON 1000D DIGITAL CAMERA FOR MULTIZONE PHOTOGRAPHY WITH SPATIALLY-RESOLVED SPECTRAL DEVICES - K. N. Kaplevskiy; M. P. Samtsov; I. M. Gulis; D. S. Tarasov (Приборы и методы измерений, 2015)
The possibility of use a CANON 1000D digital camera for multizone photography is demonstrated. It is found that a dynamic range of the recorded light intensities is varied from 260 to 3650 quantization levels of the ADC. Linearity of the light-sensitive element of the camera has been studied in dependence on its illumination and exposure time.